(3GdMLI aj HjGf GdeMLIs - (3ehab GdGSdGe CHh GdbGSe ESeGYjd eMeO Hf GdaVd Hf Ydj GdCUagGfj,J (B535 (3g` s ((3CHh GdNWGH SYO GdOjf CMeO Hf GdaVd jMji s)
(3ChdgG (B:s
(3jHOC HHGH ai GdJhMjO s
(3BNQgG (B:s
(3hbGd QLd ddTYHi EaJfG CjgG GdYGde bGd GdYGde ef jNGa Gddg gPG BNQ eG EJab EedGDg ef cJGH GdMLI ai HjGf GdeMLI s
(3HgG fXGe GdJYbjHIs
(3LeY GdeDda ajg OdGFd GdJhMjO hYbGFO Cgd GdSfIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B631s
Keywords: (3CUhd Gdabgs